Social issue under econimic transformation and integration in Vietnam (Social Labour, 2007)
This 2nd volume of Social Issues Under Econimic Transformation and Intergration in Vietnam is a collection of papers prepair by VDS staff as well as by outsite researchers. To continue disseminating important infornation to policy makers and researchers, as well as people who are interested in the development of Vietnam, the 2nd volume addresses another set of social issues that emerge as a consequence of economic development and social reforms. Five papers or chapters comprise the 2nd volume: Chapter 2 provides an evaluation of prospects and challenges of growth and poverty reduction in Vietnam since "Doi moi" ; Chapter 3 focus on the reform of the primary health care system in Vietnam by examining the attempt to rebuild the reequip several thousand community health centers in the late 1990s. Addressing one of the most pressing social issues in urban areas - Chapter 4 analuzes the real childhood of children working in the streets with information from case studies conducted in Hanoi in 2005 ; Chapter 5 is presented the analysis on the current situation of the internal migrants and their access to the formal protection system in Vietnam ; Chapter 6 focuses on the elderly population.